The Effect of Perceived Risk, Financial Knowledge and Government Support on User Interest with Perceived Usefulness as an Intervening Variable: A Study on e-Wallet Users in Sulawesi - Eka Indriyani MS; Fatma Fatma; Ruslan Hasyim (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2022)
Indonesia's economic growth still has a significant impact during the COVID-19 pandemic. Various efforts have been made by the government to prevent the spread of the virus by implementing the Large-Scale Social Restriction (PSBB) policy to the Enforcement of Community Activity Restrictions (PPKM). This is implemented to avoid crowds and all activities can only be done at home (work from home), including satisfy consumptive needs. During the pandemic, there is the right choice to transact only from home or where we are currently, namely the use of digital e-wallet payments. This study aims to analyze the effect of perceived risk, financial knowledge and government support on user’s interest of e-wallet with perceived usefulness as an intervening variable in Sulawesi Island. Data was collected through a questionnaire or google form and then analyzed using the Smart-PLS 3.0 software. The sample is 384 e-wallet users who are in the Sulawesi Island with the criteria that they have used e-wallet since March 2019 until now. The results of the study prove that of the seven direct relationships there is only one relationship does not have a significant effect, namely government support does not effects e-wallet user’s interest. While the other three indirect relationships proved to have a significant effect.